GENESIS OF URANIUM AND RARE-EARTH ELEMENT CONCENTRATIONS IN THE COAL MEASURES OF A LARGE CRATONIC BASIN - Sergeyev I.P.; Shumlyanskiy V.A. (My University, 1989)
In the cratonic basin that was studied by us, which inherited the structure of the Devonian rift trough, the Lower Carboniferous gray coal measures and overlying Lower and Middle Carboniferous carbonate and clastic deposits form large elongate synclines. In the centrocline of one fold there is a coal deposit with sizable amounts of uranium and rare-earth elements (REE). From the data of this study we can draw certain conclusions concerning the process that deposited uranium and REE in the sedimentary rocks of the lower gray coal-measure member. The localization of relatively high uranium and REE concentrations in paleostream channels indicates that the ore elements were introduced by ground water. Uranium and REE were derived from Early Carboniferous weathered mantle on the crystalline rocks rimming the sedimentary basin.
Keywords: Carboniferous; Devonian; Палеозой::Каменноугольная; Paleozoic::Devonian; Paleozoic::Carboniferous; Палеозой::Девонская